Divine discourse : philosophical reflections on the claim that God speaks - Wolterstorff, Nicholas (Cambridge, Cambridge University Press, 1995)
"Divine discourse comprises Nicholas Wolterstorff's philosophical reflections on the claim that God speaks. This claim figures large in the canonical texts and traditions of Judaism, Christianity, and Islam, but there has been remarkably little philosophical reflection on it, in good measure (so Professor Wolterstorff argues) because philosophers have mistakenly assimilated divine speech to divine revelation. He embraces contemporary speech-action theory as his basic approach to language; and after expanding the theory beyond its usual applications, concludes that the claim that God performs illocutionary actions is coherent and entails no obvious falsehoods. Moving on to issues of interpretation, he considers how one would interpret a text if one wanted to find out what God was saying thereby. Prominent features of this part of the discussion are his defense, against Ricoeur and Derrida, of the legitimacy of interpreting a text to find out what its author said, and his analysis of the double hermeneutic involved when the discourse of one person is appropriated into the discourse of another person. The book closes with a discussion of the epistemological question of whether we are entitled to believe that God speaks."--Jacket
Preface -- 1. Locating our topic -- 2. Speaking is not revealing -- 3. The many modes of discourse -- 4. Divine discourse in the hands of theologians -- 5. What it is to speak -- 6. Could God have and acquire the rights and duties of a speaker? -- 7. Can God cause the events generative of discourse? -- 8. In defense of authorial-discourse interpretation: contra Ricoeur -- 9. In defense of authorial-discourse interpretation: contra Derrida -- 10. Performance interpretation --
Includes bibliographical references (pages 297-324) and index
Keywords: Word of God (Christian theology); Speech acts (Linguistics) -- Religious aspects -- Christianity; Revelation